Effect of Functional Rehabilitation on Performance of the Star Excursion Balance Test Among Recreational Athletes With Chronic Ankle Instability: A Systematic Review - Leanne Ahern, PT, MSc (Archives of Rehabilitation Research and Clinical Translation, 2021)
Objective: To determine (1) the effectiveness of rehabilitation for chronic ankle instability as measured by the Star Excursion Balance Test (SEBT) and (2) the relative efficacy and the long-term effects of these rehabilitation interventions. Data Sources: Ten electronic databases were searched (2009-2019). Study Selection: Included articles were randomized controlled trials in English investigating recreational athletes aged ≥18 years with chronic ankle instability. At least 1 functional rehabilitation intervention had to be included and the SEBT test (or the modified version) used as an outcome measure. Data Extraction: Two researchers (L.A., O.N.) extracted data regarding participant demographics; intervention characteristics; trial size; and results at baseline, postintervention, and at follow-up, where appropriate. Data Synthesis: A systematic review and narrative synthesis was conducted. Methodological quality of included studies was assessed using the Cochrane Risk of Bias Tool and the van Tulder scale. The review was registered with PROSPERO (ID: 164468). Ten studies (n=368), 2 high-quality, 1 moderate-quality, and 7 low-quality, were included in the review. Interventions included balance training, strength training, vibration training, and mixed training. Results suggest that rehabilitation of chronic ankle instability that includes wobble board exercises (average percentage change: 14.3%) and hip strengthening exercises (average percentage change: 12.8%) are most effective. Few studies compared different types of rehabilitation for chronic ankle instability. However, improvements on the SEBT suggest that a rehabilitation program focusing on wobble board training and hip strengthening performed 3 times weekly for 4-6 weeks is the optimal rehabilitation program to improve dynamic postural control in recreational athletes with chronic ankle instability. Conclusions: Few studies directly compared different rehabilitation interventions, and there was limited long-term follow-up; therefore, the relative efficacy of different rehabilitation programs remains unclear. However, it seems that rehabilitation of chronic ankle instability should include proprioceptive and strengthening exercises of relatively short duration.